DRANS: Daily Routine Analysis for Node Searching in delay tolerant networks - Xingyu He; Guisong Yang; Hao Zhang (International Journal of Distributed Sensor Networks)
In delay tolerant networks, the success rate and the transmission speed are restricted by limited social interaction and complex node mobility pattern analysis. To increase the success rate and reduce the transmission delay in delay tolerant networks, we propose Daily Routine Analysis for Node Searching in delay tolerant networks. In Daily Routine Analysis for Node Searching, each node is required to generate a Staying Probability Table and a Transiting Probability Table by analyzing its own daily routine, then to distribute its Staying Probability Table and Transiting Probability Table to the whole network with the help of other nodes having different mobility patterns. On the basis of the Staying Probability Table and Transiting Probability Table, Daily Routine Analysis for Node Searching further provides a node tracking strategy and an opportunistic routing strategy for delivering data from the source node to the destination node. Trace-driven experiments are performed to compare Daily Routine Analysis for Node Searching with previous node searching methods. The experimental results demonstrate that Daily Routine Analysis for Node Searching is able to promote the success rate and reduce the transmission delay effectively.